2016
DOI: 10.3109/14767058.2015.1131261
|View full text |Cite
|
Sign up to set email alerts
|

Uterine fibroids at routine second-trimester ultrasound survey and risk of sonographic short cervix

Abstract: Women with uterine fibroids may be at higher risk for a short cervix. Fibroids are also associated with several adverse obstetric and neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Blitz et al investigated whether pregnant women with uterine leiomyoma are at higher risk for a short cervix. 18 According to this retrospective study, they reported 5.1% leiomyomas prevalence in pregnant patients. In this study the authors evaluated the pregnant women with gestational age of 17-23 weeks and found significantly higher short cervix (<25 mm) incidence (3.6%) in pregnant patients with leiomyoma than healthy pregnant controls (1.5%).…”
Section: Discussionmentioning
confidence: 87%
“…Blitz et al investigated whether pregnant women with uterine leiomyoma are at higher risk for a short cervix. 18 According to this retrospective study, they reported 5.1% leiomyomas prevalence in pregnant patients. In this study the authors evaluated the pregnant women with gestational age of 17-23 weeks and found significantly higher short cervix (<25 mm) incidence (3.6%) in pregnant patients with leiomyoma than healthy pregnant controls (1.5%).…”
Section: Discussionmentioning
confidence: 87%
“…Finally, 19 articles (18 studies) were included in this meta-analysis. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] One of these papers reported complementary information to the primary outcome information. 35,38 The selection process is shown in Figure 1.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
“…There were five cohort studies, including 3449 pregnant women with UF and 111 644 control women without UF reported in five articles. 26,33,35,38,41 There were also 13 case-control studies, including 10 270 pregnant women with UF and 150 795 control women without UF. 24,25,[27][28][29][30][31][32][34][35][36][37]40,42 In all included studies, the presence or absence of UF was determined by ultrasound examination during the first or second trimesters of gestation.…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations